Zgodność pomiędzy wynikami testu FMS a częstością występowania kontuzji u siatkarek na przykładzie drużyny II ligowej = The consistency between the FMS test results and the frequency of injuries in II league female volleyball players - Siedlaczek, Marcin; Srokowski, Grzegorz; Łukasiewicz, Hanna; Srokowska, Anna; Kowalik, Tomasz; Piekorz, Zuzanna; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Siedlaczek Marcin, Srokowski Grzegorz, Łukasiewicz Hanna, Srokowska Anna, Kowalik Tomasz, Piekorz Zuzanna, Zukow Walery. Zgodność pomiędzy wynikami testu FMS a częstością występowania kontuzji u siatkarek na przykładzie drużyny II ligowej = The consistency between the FMS test results and the frequency of injuries in II league female volleyball players. Journal of Education, Health and Sport. 2015;5(8):529-539. ISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.44362 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A529-539 https://pbn.nauka.gov.pl/works/688455 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 26.07.2015. Revised 05.08.2015. Accepted: 25.08.2015. Zgodność pomiędzy wynikami testu FMS a częstością występowania kontuzji u siatkarek na przykładzie drużyny II ligowej The consistency between the FMS test results and the frequency of injuries in II league female volleyball players Marcin Siedlaczek1, Grzegorz Srokowski1, Hanna Łukasiewicz2, Anna Srokowska2, Tomasz Kowalik2, Zuzanna Piekorz1, Walery Zukow3 1. Katedra Fizjoterapii, Zakład Kinezyterapii i Masażu Leczniczego, UMK w Toruniu CM im. L. Rydygiera w Bydgoszczy, ul. Techników 3, 85- 801 Bydgoszcz 2. Katedra i Zakład Podstaw Kultury Fizycznej, UMK w Toruniu CM im. L. Rydygiera w Bydgoszczy, ul. Świętojańska 20, 85- 077 Bydgoszcz 3. Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Bydgoszcz Adres do korespondencji: Marcin Siedlaczek, Katedra Fizjoterapii Zakład Kinezyterapii i Masażu Leczniczego, UMK w Toruniu CM im. L. Rydygiera w Bydgoszczy, ul. Techników 3 Bydgoszcz, marcinsied@o2.pl Grzegorz Srokowski, Katedra Fizjoterapii Zakład Kinezyterapii i Masażu Leczniczego, UMK w Toruniu CM im. L. Rydygiera w Bydgoszczy, ul. Techników 3 Bydgoszcz g.srokowski@gmail.com Słowa kluczowe: FMS, siatkówka, urazy. Key words: FMS, volleyball, injury. Summary Introduction and aim of the study: Volleyball is a team sport in which the results consist of a large number of factors. The risk of injury for daily training is very high. Volleyball is also an asymmetric sport, which further increases the risk of injury. Simple screening test, which is Functional Movement Screen, will reduce this risk, so I think that a lot of clubs will decide to implement of it. The main aim of this study is to present and compare the results of the functional assessment of motor and susceptibility to injury in female volleyball players and their interplay with injuries which happened in the last three years. Aim of the study was carried out based on the study material comprising a group of 15 women, practicing volleyball professionally. The research group age was between of 20-35 years. Material and Method: Functional Movement Screen- functional screening was the research method. It is using the seven tests which can assess the patient's/athlete’s basic movement patterns. All motion tasks are assessed on a scale 0 to 3. The players also filled the questionnaire. Results: Maximum disturbance revealed deep squat test. The smallest disorders showed shoulder mobility test for the left hand and in line lunge test for the left leg. Three of the five single limb tests showed asymmetry: hurdle step, deep squat, shoulder mobility. 53% of players have experienced a serious injury in the last three seasons. The two players with the highest number of FMS points have not been seriously injured so far. Discussion and Conclusion: The consistency between the FMS test results and the frequency of injuries in II league female volleyball players was different, then in other studies. For the participants deep squat was the most difficult test, over 50% of players had painful knees, average points in FMS test was 14,73.